CONCLUSION THE MATCHING WEIGHT FUNCTIONS FOR FIELDOF AMPLITUDES AND GRADIENTS WITH A SQUARE BASE SPECTRUM - Інфімовський, Сергій Юрійович (Eastern-European Journal of Enterprise Technologies, 2010)
The opportunity to estimate a field of errors of the observations f (x1, x2) , coordinated with fields of components of a gradient f1 (x1, x2) is considered at a square basis of a spectrum.